Kinematics and modeling of the inner region of M 83 - Rodrigues, Irapuan (2009)
Two-dimensional kinematics of the central region of M 83 (NGC 5236) were obtained through three-dimensional NIR spectroscopy with the Gemini South telescope. The spatial region covered by the integral field unit (∼5″ × 13″ or ∼90 × 240 pc) was centered approximately at the center of the bulge isophotes and oriented southeast-northwest. The Paβ emission at half-arcsecond resolution clearly reveals spider-like diagrams around three centers, indicating the presence of extended masses, which we describe in terms of Satoh distributions. One of the mass concentrations is identified as the optical nucleus (ON), another as the center of the bulge isophotes, similar to the CO kinematical center (KC), and the third as a condensation hidden at optical wavelengths (hidden nucleus, HN), coincident with the largest lobe in 10 μm emission. We run numerical simulations that take into account ON, KC, and HN and four more clusters, representing the star-forming arc at the southwest of the optical nucleus. We show that ON, KC, and HN suffer strong evaporation and merge in 10-50 Myr. The star-forming arc is scattered in less than one orbital period, also falling into the center. Simulations also show that tidal striping boosts the external shell of the condensations to their escape velocity. This fact might lead to an overestimation of the mass of the condensations in kinematical observations with spatial resolution smaller than the condensations' apparent sizes. Additionally, the existence of two ILR resonances embracing the chain of H II regions, claimed by different authors, might not exist due to the similarity of the masses of the different components and the fast dynamical evolution of M 83 central 300 pc.